THE ROLE OF FUNCTIONAL LITERACY IN THE PROCESS OF TEACHING BIOLOGICAL SCIENCES - Isagalieva , Sadafkhon Mukhammadaminovna (Innovative Development in Educational Activities, 2023)
Teaching biology is a field that requires a unique methodology. This article examines the importance, forms and development issues of functional literacy in the process of teaching biological sciences.